ANALISIS MODEL PEMBELAJARAN BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATA PELAJARAN MEKANIKA TEKNIK UNTUK MENINGKATKAN HASIL BELAJAR SISWAPADA SMK - Egi Noruza (CV. ADIBA AISHA AMIRA, 2024)
Problem Based Learning (PBL), is a learning model that is able to provide experience and an innovative learning model that can provide active learning conditions for students to solve a problem through the stages of scientific methods so that students can learn knowledge related to the problem as well as have the skills to solve problems. The subject of Engineering Mechanics is one of the productive subjects of several expertise programs related to the field of civil engineering. This subject is an applied subject that discusses the basic concepts of calculation – calculation of building structures that must be mastered by students This article aims to analyze the Problem Based Learning (PBL) based learning model in engineering mechanics subjects to improve student learning outcomes in vocational schools, Data is taken based on literature from research related to the application of Problem Based Learning Model Based Analysis Results. Problem Based Learning (PBL) is suitable for use in the teaching and learning process (KBM).